Alcea pallida WALDST. & KIT. (MALVACEAE) AS A HEAVY METAL BIOMONITOR IN ISTANBUL (TURKEY) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2010)
In this study, the biomonitoring features of 4 organs (flower, leaf, stem and root) of Alcea pallida Waldst. & Kit. (eastern hollyhock malvaceae) for the heavy metals Pb, Cd, Cu and Zn were investigated. A. pallida plant samples from 5 sites of 3 administorial districts of Istanbul were collected in summer period 2005. The heavy metal contents in the organs of A. pallida were measured by means of wet digestion procedure and atomic absorption spectrophotometry. The highest mean Pb level was found in the leaves, the lowest in the stems, as well as for Cd, in roots and flowers, and for Cu, in leaves and stems, and, finally, for Zn, in leaves and flowers, respectively. The concentrations of the corresponding soils for Pb, Cd, Cu and Zn remained within accepted normal concentration limits, whereas some Cu concentrations reached toxic values. Considering the results of the correlation analysis of the study, especially the roots of A. pallida were found to be a reliable biomarker for Cd, Cu and Zn-polluted areas.
Keywords: Eastern hollyhock; heavy metals; biomonitoring; Istanbul; ZINC; CADMIUM; LEAD; SOIL; EXPOSURE; PLANTS